2019
DOI: 10.1111/jar.12615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dementia Care Mapping on job satisfaction and caring skills of staff caring for older people with intellectual disabilities: A quasi‐experimental study

Abstract: BackgroundThe ageing of people with intellectual disabilities, involving consequences like dementia, creates a need for methods to support care staff. One promising method is Dementia Care Mapping (DCM). This study examined the effect of DCM on job satisfaction and care skills of ID‐care staff.MethodsWe performed a quasi‐experimental study in 23 group homes for older people with intellectual disabilities in the Netherlands. Among staff, we assessed job satisfaction and care skills as primary outcomes and work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 81 publications
0
14
1
3
Order By: Relevance
“…As a result, table 1 shows the included studies and their reference to the six dimensions. Open access Table 1 The presence of the six dimensions of person-centred care 37 within the person-centred care measurement tools in the included studies Dimensions* Edvardsson et al, 53 Wallin et al, 44 Røen et al, 55 Schaap et al, 48 Silén et al, 42 Sjögren et al, 43 Vassbø et al 57…”
Section: Data Extraction and Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, table 1 shows the included studies and their reference to the six dimensions. Open access Table 1 The presence of the six dimensions of person-centred care 37 within the person-centred care measurement tools in the included studies Dimensions* Edvardsson et al, 53 Wallin et al, 44 Røen et al, 55 Schaap et al, 48 Silén et al, 42 Sjögren et al, 43 Vassbø et al 57…”
Section: Data Extraction and Synthesis Of Resultsmentioning
confidence: 99%
“…41 43 44 47 49 50 55 57 Three cross-sectional studies by Edvardsson et al, 53 Elfstrand Corlin and Kazami 46 and Lewis et al 51 showed an association between job satisfaction and only subscales of PCC, that is, 'personalising care' and 'organisational support', 53 'knowing the person' and 'resident autonomy' 46 and 'quality improvement subscale' and 'work environment covariate'. 51 Three quasi-experiment studies by Dichter et al 56 , Nocon et al 52 and Schaap et al 48 found no significant improvement in job satisfaction after the PCC implementation.…”
Section: Measurement Of Staff Outcomesmentioning
confidence: 98%
See 3 more Smart Citations